IAP Antagonists Enhance Apoptotic Response to Enzalutamide in Castration‐Resistant Prostate Cancer Cells via Autocrine TNF‐α Signaling. Issue 8 (27th February 2017) - Pilling, Amanda B.; Hwang, Ok; Boudreault, Alain; Laurent, Alain; Hwang, Clara
Abstract : BACKGROUND: Castration‐resistant prostate cancer (CRPC) remains incurable and identifying effective treatments continues to present a clinical challenge. Although treatment with enzalutamide, a second generation androgen receptor (AR) antagonist, prolongs survival in prostate cancer patients, responses can be limited by intrinsic resistance or acquired resistance. A potential mechanism of resistance to androgen axis inhibition is evasion of apoptosis. Inhibitor of apoptosis proteins (IAPs) are found to be overexpressed in prostate cancer and function to block apoptosis and promote survival signaling. Novel, small‐molecule IAP antagonists, such as AEG40995, are emerging as a strategy to induce apoptosis and increase therapeutic response in cancer. METHODS: Human prostate cancer cell lines LNCaP and C4‐2 were treated with enzalutamide with or without addition of IAP antagonist AEG40995 and proliferation and survival were determined by MTS and clonogenic assay. Western blot was used to evaluate IAP protein expression changes and PARP‐1 cleavage was assessed as indication of apoptosis. Flow cytometry was performed to analyze apoptosis in treated cells. Caspase activity was determined by luminescence assay. Quantitative real‐time PCR and immunometric ELISA was used to assess TNF‐α (transcript and protein levels, respectively) in response to treatment. RESULTS: In this study, we demonstrate that IAP antagonist AEG40995 exhibits minimal effects on prostate cancer cell proliferation or survival, but rapidly degrades cIAP1 protein. Combination treatment with enzalutamide demonstrates that AEG40995 increases apoptosis and reduces proliferation and clonogenic survival in cell line models of prostate cancer. Mechanistically, we demonstrate that apoptosis in response to enzalutamide and IAP antagonist requires activation of caspase‐8, suggesting extrinsic/death receptor apoptosis signaling. Assessment of TNF‐α in response to combination treatment with enzalutamide and AEG40995 reveals increased mRNA expression and autocrine protein secretion. Blocking TNF‐α signaling abrogates the apoptotic response demonstrating that TNF‐α plays a critical role in executing cell death in response to this drug combination. CONCLUSIONS: These findings suggest that IAP antagonists can increase sensitivity and amplify the caspase‐mediated apoptotic response to enzalutamide through TNF‐α signaling mechanisms. Combination with an IAP antagonist increases enzalutamide sensitivity, lowers the apoptotic threshold and may combat drug resistance in patients with prostate cancer. Prostate 77:866–877, 2017 . © 2017 Wiley Periodicals, Inc.